2022
DOI: 10.1136/archdischild-2022-324172
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the role of the mandatory use of face covering masks for the control of SARS-CoV-2 in schools: a quasi-experimental study nested in a population-based cohort in Catalonia (Spain)

Abstract: ObjectiveTo assess the effectiveness of mandatory use of face covering masks (FCMs) in schools during the first term of the 2021–2022 academic year.DesignA retrospective population-based study.SettingSchools in Catalonia (Spain).Population599 314 children aged 3–11 years attending preschool (3–5 years, without FCM mandate) and primary education (6–11 years, with FCM mandate).Study periodFrom 13 September to 22 December 2021 (before Omicron variant).InterventionsA quasi-experimental comparison between children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…Based on the facts we have found, the use of face mask in the hope of maintaining health is unfortunately contradicting the WHO's definition of health. Regarding all the possible side effects of mask and their still unproven efficacy against viral transmission within the general population 4,[160][161][162] , health seems not to be substantially preserved by wearing face masks. So far, only two randomized controlled mask trials for prevention of SARS-CoV-2 infection in the general population have been published: one high quality study from Denmark, Europe 163 , and the other from Bangladesh with biased results and a lot of inconsistencies 164 .…”
Section: Complaints and Symptoms Under Mask Use And The Who Definitio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the facts we have found, the use of face mask in the hope of maintaining health is unfortunately contradicting the WHO's definition of health. Regarding all the possible side effects of mask and their still unproven efficacy against viral transmission within the general population 4,[160][161][162] , health seems not to be substantially preserved by wearing face masks. So far, only two randomized controlled mask trials for prevention of SARS-CoV-2 infection in the general population have been published: one high quality study from Denmark, Europe 163 , and the other from Bangladesh with biased results and a lot of inconsistencies 164 .…”
Section: Complaints and Symptoms Under Mask Use And The Who Definitio...mentioning
confidence: 99%
“…The paucity in high-quality mask studies is unfortunate. Seeing the overall weak evidence for efficacy of masks against viral transmission within the general population 4,[160][161][162][166][167][168] , face masks have to be evaluated appropriately in the sense of the Hippocratic Oath and as per the Primum nihil nocere (above all do not harm). To avoid at all costs that the damage caused by preventive or therapeutic measures becomes greater than that caused by the disease itself, should be the credo of all those involved in the containment of the crisis, including politicians and the socalled experts.…”
Section: Complaints and Symptoms Under Mask Use And The Who Definitio...mentioning
confidence: 99%
“…A new, elegantly designed, quasi-experimental study from Catalonia, Spain, by Coma et al 8 helps to shed light on the efficacy of masks for younger, school-aged children in educational settings. The benefit of this study design is that unlike other observational studies, the settings in which masks are used differ only in the age of the children; those in the first year of primary school wearing face coverings and those in the last year of preschool do not.…”
mentioning
confidence: 99%
“…Importantly, too, the findings of these studies were inconsistent with more rigorously designed observational studies 5 , 6 , 7 including a study using a regression discontinuity design which reported no significant effect of masking on SARS-CoV-2 transmission in Catalonian schools 8 . Furthermore, one randomized study in adults found no impact of community cloth masking and only a marginal impact of surgical masking, though only in those over 50 years of age 9 .…”
Section: Introductionmentioning
confidence: 74%